Facets of nativism: a heuristic exploration - Betz, Hans-Georg (Patterns of prejudice, 2019)
Contemporary radical right-wing populism is an ideational compound of anti-elite populism and nativism, the latter encapsulated in the notion that 'the own people' should come first. Like populism, nativism has proven to be a rather elusive concept, particularly when it comes to its relationship to related concepts, such as patriotism, nationalism and particularly racism. Originally developed to analyse anti-immigrant sentiments in the United States and Canada, the term 'nativism' has recently been increasingly used to understand the success of the radical populist right in Europe and elsewhere. In this article, Betz present three facets of nativism: economic nativism, centred on the notion that jobs should be reserved for native citizens; welfare chauvinism, based on the notion that native citizens should be accorded absolute priority when it comes to social benefits; and symbolic nativism, advancing the notion that government should do everything to defend the cultural identity of a given national society. Whereas, in the past, economic considerations, including concerns about the viability of the welfare state, were central to anti-immigrant sentiment, in recent years, symbolic nativism, grounded in a defence of national cultural identity, is central to the success of radical right-wing populist mobilization.